2016
DOI: 10.1027/1864-1105/a000153
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment of Narrative Engagement

Abstract: Abstract. This study investigated the validity of the narrative engagement scale ( Busselle & Bilandzic, 2009 ) by grounding the dimensions of the scale in relationships between self-reported narrative engagement and embodied mental processes occurring during exposure. Psychophysiological measures were used to observe real-time variation in mental processes activated when individuals viewed narrative content that was manipulated in two fundamental content characteristics: cohesion and emotional content. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…While this technique uses a questionnaire-based approach, physiological monitoring has been used to validate the self-reported narrative engagement scale [41].…”
Section: Narrative Engagementmentioning
confidence: 99%
“…While this technique uses a questionnaire-based approach, physiological monitoring has been used to validate the self-reported narrative engagement scale [41].…”
Section: Narrative Engagementmentioning
confidence: 99%
“…For example, not only may stronger emotional responses evoke differential patterns of cognitive responses, but a particular combination of cognitive, emotional, and/or arousal responses may even designate a qualitatively different response state (e.g., attentional, automatic, or transported, Potter, 2008) that our individual response outcomes did not tap into. More work is needed to understand how combinations of responses may reflect a theoretically relevant "higher-order" response states (e.g., enjoyment or engagement, Sukalla, Bilandzic, Bolls, & Busselle, 2016), which could then be investigated in relation to relevant individual differences.…”
Section: Consider Single Versus Combined Responsesmentioning
confidence: 99%
“…Green and Brock (2000) developed a retrospective self-report scale that captures transportation in all of these facets, of which Appel, Gnambs, Richter, and Green (2015) devised a short form with comparable reliability despite a reduced number of items. These scales are, to date, the only reliable tools to comprehensively measure the construct of transportation, although means of measuring aspects of transportation concurrently and objectively are currently being explored (e.g., Bezdek & Gerrig, 2017;Hartung, Burke, Hagoort, & Willems, 2016;Sukalla, Bilandzic, Bolls, & Busselle, 2016).…”
Section: Narrative Persuasion and The Transportation Imagery Modelmentioning
confidence: 99%
“…It would be preferable in future studies to empirically test the assumed temporal sequence by measuring transportation concurrently during exposure to the narrative. Methods for doing so are being explored, but it must be noted that none of the measures used so far are able to comprehensively capture the phenomenon of transportation, only aspects of it (e.g., the attentional or emotional components; Bezdek & Gerrig, 2017;Hartung et al, 2016;Sukalla et al, 2016), and their relationships to self-reported transportation are sometimes inconsistent (e.g., Hartung et al, 2016). Nonetheless, it seems desirable for future research to further explore the usefulness of such measures and eventually overcome the limitations imposed by retrospective self-report measures of media experiences.…”
Section: Limitationsmentioning
confidence: 99%